An Electrochemical and Spectroscopic Investigation of Nickel Electrodes in Alkaline Media for Applications in Electro-Catalysis - Hall, David Scott (Université d'Ottawa / University of Ottawa, 2014)
Nickel-based catalysts in aqueous alkaline media are low-cost electrode materials for electrolytic hydrogen generation, a renewable method of producing fuel and industrial feedstock. However, further work is necessary to develop inexpensive electro-catalyst materials with high activity and long-term stability. This thesis employs spectroscopic and electrochemical methods to directly address specific research problems for the development of improved materials and devices with commercial or industrial value. The first chapter reviews the applications of nickel electrodes; the structures of nickel, nickel hydroxides, and nickel hydrides; and techniques for measuring the electrochemically active surface area (AECSA) of nickel. In the second chapter, electrochemically precipitated nickel hydroxide materials are fully characterized by Raman spectroscopy, Fourier-transform infrared (FT-IR) spectroscopy, X-ray photoelectron spectroscopy (XPS), and X-ray diffraction (XRD). This work unifies and simplifies the large body of literature on the topic by considering two fundamental phases, α- and β-Ni(OH)2, and various types and extents of structural disorder. The third chapter examines and demonstrates the potential applications of in situ Raman spectroscopy by monitoring the spontaneous ageing of α-Ni(OH)2 to β-Ni(OH)2 in pure water at room temperature. The fourth chapter considers the longstanding problem of electrode deactivation, the gradual decrease in nickel electro-catalyst activity during prolonged hydrogen production. Voltammetric and XRD evidence demonstrates that hydrogen atoms can incorporate into the electrode material and cause structural disorder or the formation of α-NiHx and β-NiHx at the surface. The voltammetric formation of NiOx, α-Ni(OH)2, β-Ni(OH)2, and β-NiOOH surface species are examined by electrochemical and XPS measurements. The fifth chapter of this thesis presents a new method to measure the AECSA by adsorption of oxalate to the (001) surface of the surface Ni(OH)2, as evidenced by voltammetric and attenuated total reflectance (ATR) FT-IR spectroscopy measurements. The adsorbed oxalate limits the surface hydroxide to a single layer. The surface NiOOH/Ni(OH)2 reduction peak during the reverse scan may be used to accurately and precisely measure the AECSA. The error of this method is estimated at < 10 %.
Keywords: Electrochemistry; Energy; Materials Science; Surface Science; Surface Area; Electrocatalysis; Nickel Hydroxide; Vibrational Spectroscopy